Syndecan-1 Shedding by Matrix Metalloproteinase-9 Signaling Regulates Alveolar Epithelial Tight Junction in Lipopolysaccharide-Induced Early Acute Lung Injury - Zhang D (Dove Medical Press, 2021)
Dong Zhang,1 Jin-tao Zhang,1 Yun Pan,1 Xiao-fei Liu,1 Jia-wei Xu,2 Wen-jing Cui,1 Xin-rui Qiao,1 Liang Dong1,2 1Department of Respiratory, Shandong Qianfoshan Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People’s Republic of China; 2Department of Respiratory, Shandong Provincial Qianfoshan Hospital, Shandong University, The First Affiliated Hospital of Shandong First Medical University, Shandong Institute of Respiratory Diseases, Jinan, People’s Republic of ChinaCorrespondence: Liang DongDepartment of Respiratory, Shandong Provincial Qianfoshan Hospital Shandong University, The First Affiliated Hospital of Shandong First Medical University, Shandong Institute of Respiratory Diseases, Jinan, People’s Republic of ChinaEmail dl5506@126.comIntroduction: Alveolar epithelial tight junction damage and glycocalyx syndecan-1 (SDC-1) degrading are key factors to pulmonary edema of acute lung injury (ALI). Matrix metalloproteinase-9 (MMP-9) was involved in glycocalyx shedding, which was vital in SDC-1 degrading. This study aimed to investigate the effects of MMP-9-mediated SDC-1 shedding on tight junction in LPS-induced ALI.Methods: Mice were intratracheally atomized with 5 mg/kg LPS to stimulate different periods and LPS stimulation for 6 hours for further studies. A549 cells was stimulated for 6 hours by active MMP-9 protein to assess the effects of active MMP-9 protein on SDC-1 and tight junction. Afterward, the mice treated with MMP-9 shRNA or A549 cells were treated with MMP-9 siRNA before LPS stimulation for 6 hours to explore the effects on glycocalyx SDC-1 and tight junction. Moreover, the mice were treated with recombinant SDC-1 protein or A549 cells were over-expressed by pc-SDC-1 before LPS stimulation for 6 hours to explore the effects of SDC-1 on tight junction.Results: The mice persistent exposure to LPS showed that MMP-9 expression, glycocalyx SDC-1 shedding (SDC-1 decreased in alveolar epithelium and increased in the BALF), tight junction impairment, FITC-albumin infiltration, and other phenomena began to appear after 6 hours of LPS treatment in this study. The levels of SDC-1 and tight junction significantly decreased by active MMP-9 protein stimulation for 6 hours in the A549 cells. Therefore, LPS stimulation for six hours was selected for investigating the underlying effects of MMP-9-mediated SDC-1 shedding on the alveolar epithelial tight junction and pulmonary edema. Further vivo analysis showed that down regulation MMP-9 expression by MMP-9 shRNA significantly alleviated glycocalyx SDC-1 shedding (SDC-1 increased in alveolar epithelium and decreased in the BALF), tight junction (occludin and ZO-1) damage, and FITC-albumin infiltration in LPS-induced early ALI mice. The vitro results also showed that MMP-9 siRNA alleviated glycocalyx SDC-1 shedding (SDC-1 increased in cell culture medium and decreased in cell surface) and tight junction damage by downregulating MMP-9 expression in LPS-stimulated A549 cells. In addition, pretreatment with recombinant mouse SDC-1 protein significantly alleviated glycocalyx (SDC-1 increased in alveolar epithelium) and tight junction damage, and FITC-albumin infiltration in LPS-induced early ALI mice. Overexpression SDC-1 by pc-SDC-1 also significantly decreased tight junction damage in LPS-stimulated A549 cells.Conclusion: Glycocalyx SDC-1 shedding mediated by MMP-9 significantly aggravated tight junction damage, which further increased the pulmonary edema.Keywords: glycocalyx, SDC-1, MMP-9, tight junction, early ALI